Multi-Site Case Studies About Zoo and Aquarium Visitors' Perceptions of the STEM Learning Ecology. Issue 2 (3rd July 2019) - Gupta, Rupanwita; Fraser, John; Rank, Shelley J.; Brucker, Joanna Laursen; Flinner, Kate
Abstract: Informal learning institutions like zoos, aquariums, science centers, and botanic gardens are popular among the American public. Many offer science-related activities, suggesting an "ecology" of sites varying in degree with regards to science and STEM (science, technology, engineering, math) learning in general. Understanding public perceptions of the STEM learning ecology can inform decisions about increasing STEM literacy in the United States. The current qualitative study used interactive workshops to understand the public's perceptions of zoos and aquariums (Z/As) in particular, compared to other settings, for their potential to support STEM learning. Visitors identified a wide range of settings in institutions and their everyday lives where they experienced STEM learning opportunities. The primary STEM discipline they encountered was science, even though the opportunities were not explicit. They also recognized that these settings offer the potential for learning about technology, engineering, and math through staff facilitation. They distinguished Z/As from other cultural organizations because of opportunities to learn about science as it related to animals. Implications for STEM learning in informal settings are discussed for its potential to engage the public in STEM outside of the formal education context.